Proportional Pythagorean Fuzzy AHP & TOPSIS Methodology for the Evaluation of Industry 5.0 Projects - Cebi, Selcuk; Sari, Irem Ucal; Kahraman, Cengiz; Oztaysi, Basar; Onar, Sezi Cevik; Tolga, Cagri (OLD CITY PUBLISHING INC, 2024)
The term, Industry 5.0 refers to a transformation in production systems with the key priorities: human-machine collaboration, sustainability, and social responsibility. The focus of Industry 5.0 on intelligent collaboration between human operators and machines brings a potential for efficiency and innovation for companies. In order to realize these potential benefits, organizations need to initiate new projects and make new investments. From the organization's perspective, this brings a project prioritization and selection problem. The project selection problem refers to the evaluation of potential projects according to various criteria and make a decision on initiating the project. By its nature, the problem is a multi- criteria decision-making problem since it involves various criteria. In this study, a decision model involving six criteria, namely compatibility, scalability, reliability, security, cost-effectiveness, and human-machine collaboration is developed. A hybrid decision-making model that integrates Proportional Pythagorean Fuzzy AHP & TOPSIS is proposed to solve the Industry 5.0 selection problem. The sensitivity analysis, comparative analysis, and discussions with decision-makers reveal that the proposed approach provides a robust, and easy-to-use methodology.
Keywords: Proportional fuzzy sets; Pythagorean Fuzzy Sets; AHP; TOPSIS; Industry 5.0; SELECTION; Computer Science; Science & Technology - Other Topics